Service-Learning Strategies as a Mechanism to Improve the Quality of University Education and Prepare Students for the Labor Market: A Field Study at Larbi Ben M’hidi University - Oum El Bouaghi - - hadef, soumia (Journal of Social Sciences and Humanities, 2025)
This study aims to investigate the extent to which Service-Learning strategies contribute to improving the quality of university education by preparing students for integration into the job market. To achieve this goal, the descriptive approach was adopted, and a scale was used and distributed to a simple random sample consisting of 350 students from the Faculty of Human and Social Sciences at Larbi Ben M'hidi University in Oum El Bouaghi. The study results revealed that the level of application of Service-Learning strategies at Larbi Ben M'hidi University – Oum El Bouaghi is low. The current study also concluded that the role of the university professor in activating Service-Learning strategies is weak. Additionally, there is a lack of student awareness and limited benefit from the university's information regarding Service-Learning strategies, which reflects the weakness of the information and communication channels that qualify students to understand the importance of this mode of learning in their professional preparation. Furthermore, the educational programs lack practical components and materials that support the development of professional competencies. This indicates a gap between the theoretical objectives of these strategies and the level of their practical implementation within the university institution. The significance of these results lies in highlighting the urgent need to adopt Service-Learning strategies as an educational mechanism to enhance students' readiness for the job market, by proposing its integration into the curricula, organizing training courses for professors, and activating career guidance services within the university.